2017
DOI: 10.1002/hipo.22704
|View full text |Cite
|
Sign up to set email alerts
|

The CAN‐In network: A biologically inspired model for self‐sustained theta oscillations and memory maintenance in the hippocampus

Abstract: During working memory tasks, the hippocampus exhibits synchronous theta-band activity, which is thought to be correlated with the short-term memory maintenance of salient stimuli. Recent studies indicate that the hippocampus contains the necessary circuitry allowing it to generate and sustain theta oscillations without the need of extrinsic drive. However, the cellular and network mechanisms supporting synchronous rhythmic activity are far from being fully understood. Based on electrophysiological recordings f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 73 publications
2
29
0
Order By: Relevance
“…The complete expressions for all these ionic channel currents are detailed in [Giovannini et al, 2017].…”
Section: Neuron Dynamics Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete expressions for all these ionic channel currents are detailed in [Giovannini et al, 2017].…”
Section: Neuron Dynamics Modelsmentioning
confidence: 99%
“…In order to simulate the complete hippocampal formation, our model uses point neural models (single-compartment) but having realistic dynamics (conductance-based Hodgkin-Huxley neurons). Among these neurons, some have one of the membrane channel's conductance directly linked to the level of Ach (CAN, see [Giovannini et al, 2017]). The microscopic anatomy of the neurons was approximated by two compartments (the simplest shape able to generate a relatively realistic LFP through a dipolar electric field [Pettersen et al, 2012]), while the macroscopic anatomy of the hippocampal structure was reproduced by positioning and connecting the neurons in an anatomically realistic manner.…”
Section: Introductionmentioning
confidence: 99%
“…In a very recent study Giovannini et al (2017) focused on the contribution of a non-specific cation (CAN) current in pyramidal cells as critical for the maintenance of theta oscillations in the isolated hippocampus preparation. Interestingly, similar to our work here, they showed that when pyramidal cells were coupled with inhibitory cells, theta oscillations became more robust.…”
Section: Discussionmentioning
confidence: 99%
“…This electrophysiological property can be explained considering that the repertoire of ion channels that pyramidal cells express in their dendrites including HCN and Kv7 channels confer them a specific adaptive inductance (119,120). Recently Giovannini et al (2017) (121) showed that a network of pyramidal cell CAN neurons may work as a θ/γ oscillator. More specifically, it can work in three different modes of operation: a slow asynchronous mode, a synchronized θ mode and a synchronized fast γ mode.…”
Section: Experimental Studies In Acute Slices Identify Microscopic Osmentioning
confidence: 99%